Correlation of Stunting Determinants Among Children Under Five - Iin Setiawati; Dana Daniati; Selvia Nurul Qomari (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Malnutrition in Indonesia is a health problem that the government has yet to fully address. East Java's achievement for stunting is 7.51%, which is above the Nutrition and MCH Program Indicator Target for stunting in 2023 of 18.4%. The prevalence of stunting in Bangkalan was 26.2% in 2022, and decreased to 10.2% in 2023. The objective is to examine the relationship between the factors that contribute to stunting in Bangkalan. The research method used correlation analysis with a cross-sectional approach, where the independent variables and dependent variables were collected at the same time. Variables are gender of infants, nutritional status of infants, history of LBW, history of maternal anemia and CED, and stunting; research sample: 398 infants with cluster sampling technique. Research instruments: observation sheets and interviews. Regression and multivariate statistical tests were used, using logistic regression. Statistical tests for gender with stunting incidence: ρ>0.05, LBW history with stunting incidence: ρ>0.05, nutritional status with stunting incidence: ρ<0.05, anemia history with stunting incidence: ρ<0.05, and CED history with stunting incidence: ρ<0.05. The gender of the young child and the history of LBW has no relationship with stunting; nutritional status, history of maternal anemia, and CED has a relationship with stunting. The most influential factors are: Nutritional Status of Toddlers, Pregnant women's anemia history, the impact of sex on stunting in relation to toddlers' gender, and LBW's past